Analysis of The Regulation of The Minister of Health Regulation Number 24 of 2022 Concerning Medical Records in Terms of Conventional Medical Record Management - Juniati, Ni Ketut; Purwani, Sagung Putri M.E; Linawati (Jurnal Health Sains, 2023)
Health is part of basic human needs. Because without health it is difficult for a person to carry out daily activities and meet other needs in this life. The following are some sources of data/legal materials that can be used for research on the Juridical Review of the Minister of Health Regulation Number 24 of 2022 concerning Medical Records. The theoretical basis of research on the Juridical Review of the Minister of Health Regulation Number 24 of 2022 concerning Medical Records, in the Management of Conventional Medical Records, includes.